MARKETING COMMUNICATION STRATEGIES IN FACING DIGITAL BUSINESS COMPETITION - Syarifuddin; Nyi Dewi Puspitasari; Indah Sulistiani (Jurnal Komunikasi, 2024)
The business sector in this digital era is experiencing very fundamental changes in business processes as a result of the emergence of information technology. The digital era presents a variety of new challenges and unlimited opportunities for business people. Business competition in the digital era is increasingly fierce, but at the same time, digitalization opens the door for new players to enter the market easily. Marketing does not only talk about products, product prices, distribution, but also talks about how to communicate these products to the public so that they are known, bought, and then become loyal. By using marketing communication strategies, consumers can be persuaded to form brand choices, change perceptions, encourage buyers, become a means of reminding the existence of the product, where to get the product, and also to be able to maintain this segment to be loyal to the company's products. Conventional marketing strategies are carried out to convince consumers to buy the products or services offered, as well as digital marketing strategies, which have the aim of convincing consumers to buy the products or services offered and increase brand awareness of the products or services offered by using various supporting tools. and internet media